The mitral annulus disjunction of mitral valve prolapse: presentation and outcome. (25th November 2020) - Essayagh, B; Sabbag, A; Antoine, C; Benfari, G; Maalouf, J; Michelena, H; Sarano, M.E
Abstract: Background: Mitral-annulus-disjunction (MAD), often described in mitral-valve-prolapse (MVP) patients, remains incompletely defined and its clinical outcome consequences are unknown. Objectives: To assess MAD prevalence, clinical and echocardiographic characteristics, and independent impact on outcome in patients with isolated-MVP. Methods: A cohort of 595 (65±16 years, 278 female) consecutive patients with MVP and comprehensive clinical, rhythmic and Doppler-echocardiographic characterization, was identified. Primary-endpoint was overall-survival, or occurrence of ventricular-arrhythmia. To eliminate clinical differences, we matched MAD-patients 1:1 with no-MAD based on propensity score for overall survival analysis using a greedy 5-to-1 digit-matching algorithm. Results: MAD was frequent, present in 186 (31%) of MVP-patients and independently associated to bileaflet-MVP, leaflet-redundancy, younger-age, female-sex, enlarged left-ventricle-endsystolic-diameter and higher left-ventricle-ejection-fraction (all P≤0.04). Outcome primary-endpoint of survival after MVP diagnosis in matched-cohort (10-year 95±1%) was not associated with MAD presence (10-year 93±2% for no-MAD and 97±1% for MAD, P=0.4). Mortality was comparable for MAD (univariate-hazard-ratio 0.64 [0.25–1.65], P=0.4 vs. no-MAD), even adjusted-comprehensively including for MVP-characteristics (adjusted-hazard-ratio 1.17 [0.39–3.50], P=0.8). However, 220 (51%) MVP-patients were diagnosed ventricular-arrhythmia (161 with ventricular-tachycardia only) and long-term, MAD was associated with lower arrhythmia- and ventricular-tachycardia- overall freedom (adjusted-hazard-ratio for MAD 2.35 [1.75–3.15], P<0.0001 vs. no-MAD and 2.71 [1.93–3.82], P<0.0001 respectively). Hence, 10-year freedom of significant ventricular-arrhythmia in overall-cohort was severely reduced with MAD (41±4% vs. 62±3% for no-MAD). Conclusion: In this unique MVP cohort, with arrhythmia and MAD comprehensively-characterized, MAD presence was frequent and independently associated to bileaflet-MVP and leaflet-redundancy. Long-term, MAD compared to no-MAD is not independently associated with higher-mortality but to reduced arrhythmia-freedom occurrence. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Mayo Foundation